2018
DOI: 10.1038/s41435-018-0030-3
|View full text |Cite
|
Sign up to set email alerts
|

Adults with septic shock and extreme hyperferritinemia exhibit pathogenic immune variation

Abstract: Post-hoc subgroup analysis of the negative trial of interleukin-1β receptor antagonist (IL1RA) for septic shock suggested that patients with features of macrophage activation syndrome (MAS) experienced a 50% relative risk reduction for mortality with treatment. Here we seek a genetic basis for this differential response. From 1341 patients enrolled in the ProCESS trial of early goal directed therapy for septic shock, we selected 6 patients with MAS features and the highest ferritin, for whole exome sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 63 publications
3
19
0
Order By: Relevance
“…In addition, given our focus on short-term mortality as an outcome, we found that lower MAP at presentation was linked with early death and remained a consistent, early adverse predictor among patients in our cohort. We hypothesize that this is due to the fact that these patients were more likely to be suffering from systemic vasodilatory states, such as sepsis [ 23 ] or the inflammatory cytokine storm syndrome, which has been associated with severe COVID-19 and ARDS [ 24 26 ]. Interestingly, we also found that kidney dysfunction at presentation (defined as serum creatinine ≥2 mg/dL), regardless of chronicity, was the most significant extra-thoracic organ system to impact short-term mortality among hospitalized patients afflicted with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given our focus on short-term mortality as an outcome, we found that lower MAP at presentation was linked with early death and remained a consistent, early adverse predictor among patients in our cohort. We hypothesize that this is due to the fact that these patients were more likely to be suffering from systemic vasodilatory states, such as sepsis [ 23 ] or the inflammatory cytokine storm syndrome, which has been associated with severe COVID-19 and ARDS [ 24 26 ]. Interestingly, we also found that kidney dysfunction at presentation (defined as serum creatinine ≥2 mg/dL), regardless of chronicity, was the most significant extra-thoracic organ system to impact short-term mortality among hospitalized patients afflicted with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperferritinemia has been suggested to have genetic associations through pathogenic variants in genes targetable by IL1RAP and anti-C5 antibodies. 140 Type-1 interferonopathies, like heterozygous null variants in IRF7, have been shown to result in severe manifestations of seasonal influenza virus. 141 Similar monogenetic variants likely exist that lead to the individual risk of severe disease onset from SARS-CoV-2 in previously healthy patients.…”
Section: Sars-cov-2 Risk Factors and Genetics Based On Human Protein mentioning
confidence: 99%
“…18,19 We recently described the pathophysiologic basis for these observations as well as putative therapies to be considered. 2023 According to our reviews, the MOF pattern of DIC and hepatobiliary dysfunction requires 1) plasma exchange therapy to reverse coagulopathy/DIC, and to remove ferritin and free hemoglobin which together are important mediators of feed forward inflammation, 2) IVIG to neutralize DNA viremia which stimulates TLR9 activation and induces liver injury, and 3) anakinra to stop cytokine induced liver injury.…”
Section: How Do We Treat the Condition?mentioning
confidence: 99%